2011
DOI: 10.1051/0004-6361/201015941
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous quiet-Sun jets

Abstract: Context. IMaX/Sunrise has recently reported the temporal evolution of highly dynamic and strongly Doppler shifted Stokes V signals in the quiet Sun. Aims. We attempt to identify the same quiet-Sun jets in the Hinode spectropolarimeter (SP) data set. Methods. We generate combinations of linear polarization magnetograms with blue-and redshifted far-wing circular polarization magnetograms to allow an easy identification of the quiet-Sun jets.Results. The jets are identified in the Hinode data where both red-and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This conclusion is based on detecting linear polarization signals between two opposite polarity features around the detected jets. Those events were also found by Rubio da Costa et al (2015) and Martínez Pillet et al (2011a). Another explanation is the rebound of downward flows caused by the convective instability when hitting dense layers (Grossmann-Doerth et al 1998, Requerey et al 2014.…”
Section: Small-scale Magnetic Elementssupporting
confidence: 60%
“…This conclusion is based on detecting linear polarization signals between two opposite polarity features around the detected jets. Those events were also found by Rubio da Costa et al (2015) and Martínez Pillet et al (2011a). Another explanation is the rebound of downward flows caused by the convective instability when hitting dense layers (Grossmann-Doerth et al 1998, Requerey et al 2014.…”
Section: Small-scale Magnetic Elementssupporting
confidence: 60%
“…Those large velocities were, however, inferred based on a single continuum position, from which the shape of Stokes V profiles could not be sampled. The existence of these magnetic upflows was later confirmed by Martínez Pillet et al (2011b) who referred to them as photospheric jets. They made use of data from Hinode/SP (Tsuneta et al 2008), which have lower spatial resolution, but a higher spectral sampling compared to the data from SUNRISE.…”
Section: Introductionmentioning
confidence: 86%
“…In the above studies, only single-lobed Stokes V profiles were reported at the spatial locations of the rapid magnetic upflows, albeit Martínez Pillet et al (2011b) also noted observations of highly asymmetric Stokes V profiles with multiple lobes (shifted with respect to the rest wavelength position). However, they did not analyze the profiles.…”
Section: Introductionmentioning
confidence: 93%